Analysis of The Effect of Economic Growth, Literacy Rate, Life Expectation and Open Unemployment Rate on Poverty in Nias Islands - Iman Totonafo Saro Hia; Sirojuzilam Sirojuzilam; M. Syafii M. Syafii (Lafadz Jaya Publisher, 2023)
This study aims to examine and analyze the effect of economic growth, literacy rates, life expectancy rates, and open unemployment rates on poverty in the Nias Islands. The type of data used in this study is a type of quantitative data with secondary data. The objects of this research are four districts and one city in the Nias Islands. This study uses panel data (Pooled Data) , which combines Time Series and Cross Section data for 12 years, namely from 2010-2021. The variables used are Economic Growth, Literacy Rate, Life Expectancy Rate, Open Unemployment Rate, and Poverty. The analytical method in this study uses the Fixed Effect Model (FEM), using E-views 10 as an estimation tool. The estimation results show that Economic Growth has a negative and significant effect on Poverty, Literacy Rate has a positive and insignificant effect on Poverty, Life Expectancy has a negative and significant effect on Poverty, Open Unemployment Rate has a positive and significant effect on Poverty. Then there is a relationship between Economic Growth, Literacy Rate, Life Expectancy, and the Open Unemployment Rate with Poverty of 92.17% while the remaining 7.83% is explained by other variables not included in the model.